MENINGKATKAN MOTIVASI DAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN KETERAMPILAN ANYAM DENGAN MENGGUNAKAN MEDIA RANCANGAN (MEDIA BY DESIGN) PADA KELAS VIII 7 SMPN 17 PADANG - FATMAWITA, Drs. Yusron Wikarya, M.Pd, Drs. Efrizal, M.Pd (Serupa The Journal of Art Education, 2014)
The purpose of this study was to :1) determine the implementation of learning skills through the use of media design (media by design) to increase students' motivation eighth grade 7 SMP 17 Padang, 2) knowing improving student learning outcomes in literacy classes in eighth grade 7 SMP 17 Champaign using media design (media by design). The results obtained from the processing of the data showed an increase in students' motivation and learning outcomes. The average score students' motivation in the first cycle was 64.78 % with a qualifying medium, increased to 83.48 % with the high category on the second cycle. The average value of student learning outcomes in the first cycle of 74.56 increased to 79.52. The number of students who have not completed the first cycle as many as 14 people (51.85 %) after the second cycle all students completed . Based on these findings it can be concluded that a significant increase in students' motivation berdampa on improving student learning outcomes. With the increase in value, then there is a positive relationship between motivation and learning outcomes achieved by students of class VIII 7 SMP 17 Padang.Kata kunci : Motivation, Learning Outcomes, Media Design (Media By Design)